PENGARUH PENERAPAN MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE (RTE) TERHADAP MOTIVASI BELAJAR PKN SISWA KELAS VII SMP NEGERI 25 PEKANBARU - Masitoh, Siti; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low level of motivation of students in Pekanbaru 25 Middle School, experimental research entitled The Effect of Application of Rotating Trio Exchange (RTE) Learning Model on PKn Learning Motivation. PKn learning motivation of class VII students in Pekanbaru State Middle School 25. The formulation of the problem in this study is "Is there an effect of the application of the Rotating Trio Exchange (RTE) learning model to PKn learning motivation of Grade VII students of Pekanbaru State Junior High School 25?". The population in this study were grade VII students in SMP Negeri 25 Pekanbaru as many as 9 classes and those taken as sample classes were as many as 2 classes taken based on the "Random Sampling" technique. Data analysis used to determine the magnitude of the increase in PKn learning motivation of class VII students was analyzed by means of descriptive data analysis and statistical analysis. Based on the analysis of the different test "t" the two sample classes namely the experimental class and the control class indicate that t count> t table (12.41> 1.66), which means that there is a significant effect at a significant level of 95%. So from that there is indeed a difference in the learning motivation of the control class students with the experimental class. So, the difference in learning motivation of students using the Rotating Trio Exchange (RTE) learning model is better than learning motivation using conventional methods.Key Words: RTE Learning Model, Learning Motivation